Pendidikan Islam Masa Penajahan Kemerdekaan dan Dinamika Kebijaksanaan - Agustang; Bahaking Rama; Muhammad Yahdi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
Researchers are interested in researching this in order to find out: Islamic education during the colonial era of independence and the dynamics of wisdom. aims to find out about: how Islamic education was during the Dutch colonial period and the Japanese colonial period, the development of Islamic education during the Dutch colonial and Japanese colonial periods, the development of Islamic education during the independence period and the development of Islamic education during the dynamics of policy. The results of this study indicate that, in the mid-19th century M. the development of educational institutions reached a high level. This is due to the increasing number of pilgrims to Mecca which has resulted in many people who are experts in the field of religion opening educational institutions. After the Dutch left Indonesia, the Japanese movement emerged. Japan gave a lot of tolerance towards Islamic education in Indonesia, equal education for indigenous people, the same as residents or children of rulers, even Japan taught a lot of self-defense skills to Indonesian youth. In the current curriculum (reform), Religious Education material has undergone significant changes from the previous curriculum (old order and new order). The study material includes: divinity, human beings, law, human rights, democracy, culture, politics, science, technology and art, inter-religious harmony, etc., these topics are studied from an Islamic perspective (for adherents of other religions, using the perspective each religion with the same topic)